Secured Cloud Storage via Attribute-based Encryption - Sowmya, B; Madhavi, K (International Journal of Computer Sciences and Engineering, 2025)
Cloud storage services have become increasingly popular. Because of the importance of privacy, many cloud storage encryption schemes have been struggle to protect data from the attackers. All of that schemes assumed that cloud storage providers are safe and it won’t be target by the attackers; however, in practice, some government (i.e., coercers) may force cloud storage providers to expose user secrets or private data on the cloud, thus altogether avoid storage encryption schemes. In this paper, we present our design for a new cloud storage encryption scheme that enables cloud storage providers to create authentic fake user secrets to protect user privacy. By utilizing our systems scrambled information can be up to conﬁdential regardless of the possibility that the capacity server is endowed; in addition, our techniques are secure against agreement assaults. Since coercers can't reveal if got privileged insights are valid or not, the distributed storage suppliers guarantee that client protection is still safely ensured. And we are also providing secret key mechanism which is aspired by KDC (Key distribution Center) one of the module and also authentication for each user to make the more secured and confidential. Were also captured the unauthorized attackers’ information also.